Tensile properties and water absorption of Gigantochloa Scortechinii bamboo strip with epoxy layer coating under sea water conditions - Rajes K.M. Rajan; Rozli Zulkifli; Mohd Faizal Mat Tahir; Albert Uchenna Ude (Results in Engineering)
Bamboo is a promising material for marine structures, but its durability is challenged by the high salinity of seawater. This study investigates the tensile properties and water absorption behavior of Gigantochloa Scortechinii bamboo strips coated with one or two layers of epoxy, exposed to varying seawater salinity levels (100 %, 50 %, and 0 %). Prior to coating, the bamboo strips underwent heat treatment at 160 °C, 170 °C, and 180 °C. The results show that bamboo treated at 170 °C and coated with two layers of epoxy significantly improved tensile strength, with a 108.16 % increase before seawater immersion and a 96.92–98.46 % improvement after immersion in 0 % salinity seawater. Tensile strength decreased more in higher salinity levels (50 % and 100 %), despite lower water absorption in these conditions. The study also found reduced water absorption and thickness swelling in bamboo strips treated at 170 °C with a double epoxy coating. Fourier Transform Infrared Spectroscopy (FTIR) confirmed chemical changes due to heat treatment and successful epoxy deposition, while Field Emission Scanning Electron Microscopy (FESEM) revealed that the double epoxy coating created a smoother surface, effectively sealing pits and micro-cracks. However, prolonged seawater exposure caused the epoxy to peel. Overall, the findings demonstrate the potential of treated and epoxy-coated bamboo as a sustainable and eco-friendly alternative to conventional materials for marine applications.